2014
DOI: 10.28945/2024
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Conceptual Framework for Evaluation of E-Content of Virtual Courses: E-Learning Center of an Iranian University Case Study

Abstract: The purpose of this study is to obtain suitable quality criteria for evaluation of electronic content for virtual courses. We attempt to find the aspects which are important in developing e-content for virtual courses and to determine the criteria we need to judge for the quality and efficiency of learning objects and e-content. So we can classify the criteria and formulate conceptual framework for evaluation of e-content. Considering the literature, we identify suitable quality criteria and then apply Delphi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…3 The above results are consistent with the results of Alsaidi [19] who showed that standards met in his study are: (1) Availability of well-stated course specification; 2The course goals and objectives are clearly stated; (3) The learning outcomes are clearly stated; (4) Accuracy; (5) Objectivity; (6) Newness of the content; 7The inclusion of all important topics. However, the above results are inconsistent with the findings of Akhavan and Arefi [20]. Appropriateness of content to E-learning standards has been given less priority by the course developers in the selected courses than other dimensions.…”
Section: IVcontrasting
confidence: 83%
See 1 more Smart Citation
“…3 The above results are consistent with the results of Alsaidi [19] who showed that standards met in his study are: (1) Availability of well-stated course specification; 2The course goals and objectives are clearly stated; (3) The learning outcomes are clearly stated; (4) Accuracy; (5) Objectivity; (6) Newness of the content; 7The inclusion of all important topics. However, the above results are inconsistent with the findings of Akhavan and Arefi [20]. Appropriateness of content to E-learning standards has been given less priority by the course developers in the selected courses than other dimensions.…”
Section: IVcontrasting
confidence: 83%
“…Akhavan and Arefi [20] conducted a study to obtain quality criteria for evaluation of electronic content for virtual courses. The study identified 22 criteria that were classified into four groups as follows: (1) quality of content and information; (2) appropriateness of content to strategy; (3) appropriateness of content to the instructional design; (4) appropriateness of content to E-learning standards.…”
Section: [D] Bl External Environmentmentioning
confidence: 99%
“…The methodology in this work is similar to the one followed by Akhavan and Arefi who have presented a framework for the evaluation of e-content [23]. Their framework has come as a result of a critical review followed by a two rounds Delphi study.…”
Section: Methodsmentioning
confidence: 99%
“…The first step involves the formation of the first edition of the DLOs' evaluation tool. It is based on the study of general purpose [16,[19][20][21][22] and discipline based [23] evaluation tools as well as on their relevant empirical studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation